(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: MMA is an intermittent sport with short, intense phases of activity repeated for 3-5 rounds of 5 minutes each, separated by 1-minute breaks. This complexity demands diverse physical skills (power, strength, speed, endurance) and metabolic processes (anaerobic, aerobic) in practice and competition. Purpose: To determine the impact of a sports-specific strength and conditioning (S&C) training regimen on MMA competitors’ performance. Materials and Methods: A total of 30 MMA athletes were selected. 1RM strength test, medicine ball throw and vertical jump test were used as outcome measures.30 players were divided into two groups. Sports Specific S&C protocol (S&C group) and general strength training (conventional group) for a period of 8 weeks. Results: Post mean and standard deviation of 1RM (bench press, squat), Medicine Ball throw and vertical jump test of S&C and conventional group were 108.3 ± 3.68, 99.93 ± 5.22, 11.80 ± 0.41, 46.27 ± 2.22 and 99.87 ± 2.77 , 93.0 ± 4.71, 10.1 ± 0.78, 42.87 ± 3.34 respectively. The S&C group were more significant than the conventional group with p value < 0.001. Conclusion: It has been concluded that the sports-specific S&C training had a positive impact on performance among MMA athletes.